Grip cup holder project / Muhammad Naufal Asyraf Mat Nasir - Mat Nasir, Muhammad Naufal Asyraf (2022)
This study is to design and fabricate any daily life problem using Mechanical Engineering Design Process. It will inspire people to design a grip cup holder. This research is about a product that can be used to hold any drinking vessels on it. The main factor to create this product is to prevent a few problems faced by any person. Some of the problems are there is not enough space or room during working at their workplace, with this statement alone people tend to make mistakes by spilling their drinks. Based on the issues, an upgraded cup holder should be designed and modified to tackle the difficulty that people have been experiencing. So, the result of this project is to fabricate the grip cup holder to solve the problems involved. The product will be tested until it meets all of the goals.